Evaluasi Kadar Kalsium dan Fospor pada Telur Itik Asin dengan Penambahan Ekstrak Daun Pandan dengan Konsentrasi yang Berbeda - Ahmad, Amiruddin; Kadir, Muh. Jurhadi (Fakultas MIPA UNM, 2020)
Abstract. This study aims to determine the use of pandan leaf extracts to evaluate the levels of calcium and phosphorus of salted duck eggs. The results showed that the effect of the addition of leaf extracts on the evaluation of calcium levels and phosphorus levels in salted duck eggs with different concentrations, did not have a significant effect or had no significant effect (P> 0.05) on calcium content, T0 treatment was not significantly different from T1, T2 and T3 and vice versa. even so but it still has an increase in calcium levels. Treatment of calcium levels from lowest to highest are T1 (0.15%), T0 (0.16%), T3 (0.17%) and T2 (0.17%). Phosphorus levels in salted duck eggs given pandan leaf extract with different concentrations have a very significant effect (P <0.05) on the phosphorus content, T0 treatment is significantly different from T1, T2, and T3, T1 is significantly different from T0 and T3 but not significantly different from T2, T2 is significantly different from T0 but not significantly different from T1 and T3, T3 is significantly different from T0 and T1 but not significantly different from T2. even so but it still has an increase in calcium levels. Calcium levels from lowest to highest are T0 (0.19%), T3 (0.23%), T2 (0.23%) and T1 (0.26%). The conclusion is that the treatment of the addition of fragrant pandan leaf extract can not affect calcium levels but affect the levels of phosphorus salted duck eggs. The best treatment is T3 treatment (30% pandanus fragrant leaf extract) with a value of 0.16 calcium levels and a value of phosphorous content 0.22. Keywords: Salted eggs, pandan leaves, calcium, phosphorus.